Pengaruh Perkembangan E-Commerce Terhadap Pola Konsumsi Gen-Z - Aqsha Raskeyna Tigan; Ayla Shafiyya Cardina; Candro Samuel Nainggolan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study examines the influence of e-commerce developments on the consumption patterns of Generation Z in Indonesia, the first generation to grow up in the digital era with widespread access to technology, the internet, and social media. Using a literature review method and a qualitative descriptive approach, this study analyzes various factors influencing Gen Z's consumption behavior through e-commerce platforms such as Shopee, Tokopedia, and TikTok Shop. The findings indicate that easy access, attractive promotions such as flash sales, and interactions through social media encourage impulsive consumer behavior. However, e-commerce also has a positive impact in the form of opportunities for the development of digital MSMEs that empower the younger generation economically. Furthermore, the COVID-19 pandemic has accelerated the adoption of online shopping, changing consumption patterns and opening new opportunities for MSMEs. The main challenge faced is the risk of impulsive buying, which can lead to financial and mental health problems. Therefore, financial literacy education and digital marketing regulations are essential to shaping healthy and sustainable consumption patterns for Generation Z. This study provides insights for the government, business actors, and the public in optimizing the benefits of e-commerce while minimizing its negative impacts.